Comments on media trends in South Africa based on AMPS 1976-1980 - Thomas Oosthuizen (Communicare)
In this article, which is based on data obtained from the annual AMPS projects of the SAARF, media trends in South Africa is commented on. It is observed that while the media use among the Coloureds, Whites and Asians is declining (all media except television), blacks show an overall increase in media use. This trend is observed in daily newspaper reading (although there was a slight decrease for blacks in the last year), radio listening, television viewing and cinema attendance, even though it is slight in instances. These trends suggest that reasons have to be determined for the increasing alienation between die media and sectors of the population. In a country where most media are primarily aimed at the whites, these trends also stress the need for media which will serve the interests of blacks.